Availability of Old Natural Rubber Tree for Biomass Power Generation - FUKUYO, Kazuhiro; HIROHATA, Nobuo (MACRO REVIEW, 2022)
As the development of alternative energy becomes an important challenge, the biomass power generation attracts attention. Old natural rubber trees will be expected as one of the woody biomass fuels for power generation plants. Some old natural rubber trees are used for household furniture as laminated lumber, while, others are sometimes left because of the difficulties of cutting, transportation and processing. Funding for replantation of old natural rubber trees expects them to be utilized for the biomass power generation.